2019
DOI: 10.1002/cbic.201900033
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Enzymatic Cyclization of Disulfide‐Rich Peptides by Using Peptide Ligases

Abstract: Disulfide-rich macrocyclic peptides-cyclotides, for examplerepresent ap romisingc lass of molecules with potential therapeutic use. Despite their potential their efficient synthesis at large scale still represents am ajor challenge. Here we report new chemoenzymatic strategies using peptide ligase variants-inter alia, omniligase-1-fort he efficient and scalable one-pot cyclization and folding of the native cyclotides MCoTI-II, kalata B1 and variants thereof, as well as of the q-defensin RTD-1. The synthesis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…Therefore, the cyclization reaction is easily scaled up to produce quantitative yields (Nuijens et al, 2016). Omniligase-1 has been successfully utilized for the backbone cyclization and oxidative folding of the disulfide-rich peptides, MCoTI-II, RTD-1, katala B1, and their variants in a one-pot reaction (Schmidt et al, 2019). Furthermore, several backbone macrocyclic peptides containing D-amino acids, isopeptide bonds, and non-peptidic moieties such as polyethyl glycol could be efficiently cyclized (Schmidt et al, 2017).…”
Section: Figure 2 | (A)mentioning
confidence: 99%
“…Therefore, the cyclization reaction is easily scaled up to produce quantitative yields (Nuijens et al, 2016). Omniligase-1 has been successfully utilized for the backbone cyclization and oxidative folding of the disulfide-rich peptides, MCoTI-II, RTD-1, katala B1, and their variants in a one-pot reaction (Schmidt et al, 2019). Furthermore, several backbone macrocyclic peptides containing D-amino acids, isopeptide bonds, and non-peptidic moieties such as polyethyl glycol could be efficiently cyclized (Schmidt et al, 2017).…”
Section: Figure 2 | (A)mentioning
confidence: 99%
“…In the same article, the one pot synthesis and folding of the natural occurring cyclotide MCoTI-II at multi gram scale was described as well as the combination of Omniligase-1 catalyzed cyclization with chemical rigidification using tris(bromomethyl)benzene. Later, other disulfide rich peptides such as kalata B1 and RTD-1 were synthesized and successfully folded to their native conformations (Schmidt et al, 2019). It was shown that due to the broad substrate scope and traceless ligation, different sites could be used to synthesize the cyclic peptides.…”
Section: Subtilisin-derived Variantsmentioning
confidence: 99%
“…where cyclic precursors (CPs) are synthesized using SPPS then cyclized in vitro by native or engineered peptide ligases such as bacterial sortase, 22,23 trypsiligase, 24,25 subtiligase 26,27 or asparaginyl endopeptidases (AEPs). [28][29][30] Pawlas et al demonstrated that peptide ligases are sustainable and economically viable in large scale manufacturing of a therapeutic peptide.…”
Section: Introductionmentioning
confidence: 99%